'That's when we started using the living room': Lessons from a local history of domestic heating in the United Kingdom. (June 2017) - Kuijer, Lenneke; Watson, Matt
Highlights: Detailed analysis of historical change across infrastructures and practices reveals processes underpinning increasing demand for heat. Spatial differentiation, automation, and novel practices fuelled demand for heat in UK council homes between 1920 and 1970. Focusing on patterns of practice reveals new insights for contemporary energy policy addressing domestic heat consumption. Abstract: Indoor climate control forms a major share of residential energy demand. Policy measures to curb this demand tend to focus on energy-efficient technologies. However, while the energy efficiency of domestic heat provision in the United Kingdom (UK) has increased considerably over the past century, demand for space heating has increased as well. This paper offers a distinctive explanation of increasing levels of domestic demand for space heating. It is grounded in a case study on changes in social housing design and use in the UK between 1920 and 1970. Based on detailed analysis of the co-evolution of housing circumstances, heating provision and patterns of everyday practice, the paper argues that increases in demand for space heating can be understood as a spreading of such demand over domestic space and time. In explaining this spread, it identifies three key contributing processes, comprising: 1) materialisations of ideals of separating domestic activities; 2) delegations of work and control to infrastructures and appliances; and 3) shifts towards more indoor, sedentary activities. It closes by considering how understanding these processes historically can inform contemporary energy policy to curb domestic energy demand for heating, and how the distinctive approach taken has implications for energy research.